(untitled) (Journal of Bangladesh Institute of Planners, 2014)
Rajshahi is the 4th largest metropolitan city of Bangladesh. It was one of the first Municipalities in Bangladesh, established in 1876 and declared as a City Corporation in 1987. To ensure planned development of the infrastructures and community facilities a number of organizations are working within the city area. In spite of this the city seems to be facing a lot of problems. Therefore a questionnaire survey was conducted to evaluate the performance of the community facilities provided by the local level institutions (RCC and RDA) of Rajshahi. This study used to measure the performance of nine urban facilities: waste management, road network, recreation facilities, Katcha Bazar, Health facilities, community center, water supply, drainage, street lighting. The performance of these services is ranked using improvement and satisfaction index values. Later a number of GIS maps are generated to show the variation of the level of improvement and satisfaction for the community facilities in the core and fringes of the city. The study shows that among all the community facilities a significant improvement is occurred in the road networks, street lighting and waste management system and the level of satisfaction is also high for these facilities. The study provides a clear portrait of the performance of the community facilities by city core and fringe that will help the local level institutions to provide the facilities in the underprivileged areas of the city. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 1-16